Contribution to the knowledge of the Estonian and Lithuanian tortricid fauna (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The list of 125 species of Lepidoptera Tortricidae collected from 1974 to 1998 in Estonia (32) and Lithuania (110) is reported. Aethes piercei Obraztsov, 1952, Aethes moribundana (Staudinger, 1859), Lozotaenia cupidinana (Staudinger, 1859), Phiaris stibiana (Guenée, 1845), Pseudophiaris sappadana (Della Beffa & Rocca, 1937), Eucosma scutana (Constant, 1863), Rhyacionia miniatana (Staudinger, 1871), Dichrorampha vancouverana McDunnough, 1935, and Dichrorampha obscuratana (Wolff, 1955) are recorded for the first time in Lithuania.
Keywords: Lepidoptera Tortricidae; fauna; Estonia; Lithuania; new records